Sistem Pakar Diagnosa Penyakit Kulit Dengan Menggunakan Metode Forward Chaining - Erni; Affandi Agung Laksono; Muchlas Syahlanisyiam; Perani Rosyani (Shofanah Media Berkah, 2023)
Decisions in the modern day can be made more quickly, efficiently, and accurately thanks to the use of computers for data processing. The techniques used in computer processing, such as AI technology (artificial intelligence method), are well-known. Health is of paramount importance to everyone, and technical advancements in the medical profession are necessary in light of current technological breakthroughs. A dermatologist can't do his or her job without the aid of healthcare IT. An expert system is a kind of artificial intelligence that employs data, facts, and reasoning strategies often reserved for humans in order to find answers to questions that would otherwise need human intervention. Forward Chaining is used by this specialized computer program. One way to reason from a problem to a solution is through forward chaining, an inference technique. Forward Chaining requires a set of rules to be followed in order, with each rule being applied in turn until the last condition is fulfilled and the search is terminated. The goal of this research is to assess a forward chaining method-based skin disease expert system utilizing data gathered from 2018-2023 in relevant publications. In this study, we used the Systematic Literature Review (SLR) method. Systematic literature review (SLR) is a research technique used to systematically collect, evaluate, and synthesize information from a large number of related scientific articles or publications. To obtain results that are more objective and accountable, this method seeks and selects relevant materials according to established procedures. The role of the computer is needed to provide fast, precise and accurate information. One of them is the development of an expert system (Expert System) which is a new breakthrough in the computer world. Expert System is a computer application that provides suggestions and solutions for solving problems.